The Prince and the Sufi : The Judeo-Persian Rendition of the Buddha Biographies - Yasharpour, Dalia, (The Brill Reference Library of Judaism ;, 2021)
The Prince and the Sufi is the literary composition of the seventeenth-century Judeo-Persian poet Elisha ben Shmūel. In The Prince and the Sufi: The Judeo-Persian Rendition of the Buddha Biographies , Dalia Yasharpour provides a thorough analysis of this popular work to show how the Buddha's life story has undergone substantial transformation with the use of Jewish, Judeo-Persian and Persian-Islamic sources. The complete annotated edition of the text and the corresponding English translation are thorough and insightful. This scholarly study makes available to readers an important branch in the genealogical tree of the Buddha Biographies.